Relation Affective Entre Apprenant-Enseignant: Cas De Certains Lycees De CÈte d`Ivoire - Patrice Aime, Djelle Opely (European Scientific Journal, ESJ, 2016)
This article is meant to work on teacher-learner relationship and the outcomes of the student-knowledge. The aim is to determine the impact of the teacher-learner relationship on the good atmosphere on creating a good learning environment in the learning process. The assumption is that teacher’s positive attitude toward learners always favours a good learning atmosphere environment. Our methodology will be based on semi directive interviews, questionnairs and inquiries on the class beginning atmosphere, classroom chronicles and evaluations meant to teachers and students in some middle schools and high schools schools in Côte d’Ivoire. The results tell us that emotion in teacher-student relationship plays various roles in the reasoning-learning process, for « they are the heart of human beings mental life ».